DIGITAL DEATHSCAPES: A TRANSDISCIPLINARY STUDY ON DEATH AND MOURNING, WORLDVIEWS, AND IDENTITIES ON FACEBOOK - Santos, Rafael Ibe (Sanata Dharma University, 2025)
In this cyberethnography and computer-mediated discourse analysis, I explored the common digital deathscapes on Facebook and how they (re)configure death and mourning in the absence of rituals in physical spaces. I also investigated social realities, worldviews, and identities constructed by the virtual semiotic resources. Results of the transdisciplinary investigation illustrate that digital mourners resort to seven repertoires of semiotic digital deathscapes, with candles and text being the most prevalent. Avoidance of death discourse emerged as a common social reality, and belief in God and the afterlife constitute the grievers’ worldviews. In terms of computer-mediated communication, two interesting impressions were uncovered. First, Facebook appears to be a platform for women, as seen in their predilection for social media engagement and virtual mourning. Conversely, men are less engaged in virtual mourning. The results highlight gender-based differences in digital grief expressions. Additionally, they underscore the prominent role of women in emotionally charged social and family events such as death and memorialization. Findings have theoretical implications on semiotics and critical discourse analysis in the context of digital mourning while also offering rare Facebook data on the subject.